Novel process for the extraction of lithium from beta-spodumene by leaching with HF - Rosales, Gustavo Daniel (2014)
In this study lithium was extracted from β-spodumene with hydrofluoric acid leaching. The operating parameters studied were: solid–liquid ratio, stirring speed, particle size, temperature, reaction time and HF concentration. Reagents and products were characterized by X-ray diffraction (XRD), X-ray fluorescence (XRF), atomic absorption spectroscopy (AAS), scanning electronic microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS). The lithium extraction efficiency of 90% could be reached with solid–liquid ratio, 1.82% (w/v); temperature, 75 °C; HF concentration, 7% (v/v); stirring speed, 330 rpm and reaction time, 20 min. Al and Si can be precipitated as Na3AlF6 and Na2SiF6 with a recovery of 92%. Lithium carbonate was separated from leach liquor by carbonatation and crystallization during water evaporation, with recovery values of 90%, approximately.